The rotor-stator type hydrodynamic cavitation reactor approach for enhanced biodiesel fuel production. (1st January 2021) - Samani, Bahram Hosseinzdeh; Behruzian, Mehrsa; Najafi, Gholamhassan; Fayyazi, Ebrahim; Ghobadian, Barat; Behruzian, Ava; Mofijur, M.; Mazlan, Mohamed; Yue, Jun
Abstract: Today renewable energies such as biodiesel have considerable role in the bio-based economy. Long production time and low efficiency are a number of problems in biodiesel production that is essential to be considered when designing and operating the biodiesel production systems. In this study, using safflower oil in a hydrodynamic cavity reactor, biodiesel fuel was produced in the possible shortest time and maximum efficiency. The effect of reaction time (30, 60 and 90 s), concentration of potassium hydroxide catalyst (0.75%, 1% and 1.25%), alcohol to oil ratio (6, 8 and 10) and rotor-stator distance (1 cm, 2 cm and 3 cm) on the reaction yield were analyzed. The results were analyzed by response surface methodology. Among the independent variables, reaction time was the most important factor on the reaction yield, which had a positive impact on the quality of methyl ester. The optimum values obtained were: 63.88 s reaction time, 0.94% catalyst concentration, 1: 8.36 alcohol to oil molar ratio, 1.53 cm rotor-stator distance, and 89.11% yield. Several properties and compounds of biodiesel obtained were measured and compared with ASTM D6751 (American Society for Testing and Materials) and EN 14214 standard (European Standards). The results showed that most of the features conform to the afore-mentioned standard. Therefore, transesterification of safflower oil with a hydrodynamic cavitation reactor can function as a good alternative to the diesel.